A cross-sectional survey to investigate community understanding of medical research ethics committees. Issue 7 (20th January 2015) - Fritschi, Lin; Kelsall, Helen L; Loff, Bebe; Slegers, Claudia; Zion, Deborah; Glass, Deborah C
Abstract : Study explanatory forms often state that an ethics committee has approved a research project. To determine whether the lay community understand the roles of ethics committees in research, we took a cross-sectional national sample from three sampling frames: the general population (n=1532); cohort study participants (n=397); and case–control study participants (n=151). About half (51.3%) of the participants had heard of ethics committees. Those who had were more likely to be those who had participated in previous surveys, older participants, those born in Australia and those with higher education. Almost all participants agreed that the roles of an ethics committee were to protect participants' privacy and ensure no harm came to study participants and most agreed that the committee's role was to ensure that the research was capable of providing answers. Case–control and cohort participants were more likely than the general population to consider that the role of an ethics committee was to design the research and obtain research funding. Overall, we found that about half of the population are aware of ethics committees and that most could correctly identify that ethics committees are there to protect the welfare and rights of research participants, although a substantial minority had some incorrect beliefs about the committees' roles. Increased education, particularly for migrants and older people, might improve understanding of the role of ethics committees in research.